2021
DOI: 10.1617/s11527-021-01615-y
|View full text |Cite
|
Sign up to set email alerts
|

Steel fibers for replacing minimum reinforcement in beams under torsion

Abstract: This paper concerns an investigation on six large-scale Steel Fiber Reinforced Concrete (SFRC) beams tested in pure torsion. All beams had longitudinal rebars to facilitate the well-known space truss resisting mechanism. However, in order to promote economic use of the material, the transverse reinforcement (i.e. stirrups/links) was varied in the six large scale beams. The latter contained either no stirrups, or the minimum amount of transverse reinforcement (according to Eurocode 2), or hooked-end steel fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…With this material, one can produce elements in almost every shape, with sufficient durability and improved mechanical characteristics (e.g., [ 7 , 8 , 9 , 10 , 11 ]). Principal applications of SFRC include industrial floorings, structures in seismic zones or underground construction and applications where structures are exposed to torsion, impact or fatigue (e.g., [ 12 , 13 , 14 ]). One disadvantage of this type of construction material is the huge influence of fibre content, distribution and orientation on its mechanic properties (e.g., [ 15 , 16 , 17 , 18 , 19 ]).…”
Section: Introductionmentioning
confidence: 99%
“…With this material, one can produce elements in almost every shape, with sufficient durability and improved mechanical characteristics (e.g., [ 7 , 8 , 9 , 10 , 11 ]). Principal applications of SFRC include industrial floorings, structures in seismic zones or underground construction and applications where structures are exposed to torsion, impact or fatigue (e.g., [ 12 , 13 , 14 ]). One disadvantage of this type of construction material is the huge influence of fibre content, distribution and orientation on its mechanic properties (e.g., [ 15 , 16 , 17 , 18 , 19 ]).…”
Section: Introductionmentioning
confidence: 99%
“…3. The experimental setup for torsion tests is a commonly used in literature [15,31,32]. The load was applied through a diagonal placed steel spreader beam.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the addition of 30 kg/m 3 and 60 kg/m 3 of steel fiber increased the θ u value by 20% and 118.8%, respectively, relative to the reference sample. The researchers reported that the addition of steel fiber contributed significantly in the increase the maximum resisting torque and maximum twist of RC beams under purer torsion[31,32,36]. The addition of steel fiber also increased torsional moment at cracking (T cr ) and the angle of twist per unit length at cracking (θ cr ).…”
mentioning
confidence: 99%
“…Equilibrium of the shearing stresses along the sections equivalent hollow tube (see Figure 1c) requires Tgoodbreak=2qAo, where A o is the area enclosed by the centerline of the shear flow path and is taken as Ao=()btc()htc refer to Figure 1c. Testing by Amin and Bentz 9 and Facconi et al 10,11 highlighted the benefits of fibers in preventing cover spalling in FRC members subjected to torsion. Therefore, unlike space truss models for plain RC, which wholly or partially discount the concrete cover in resisting the applied torsion, T , 12 in this article, we assume the thickness of the equivalent hollow tube section, t c in FRC members as tcgoodbreak=0.75Agp, where A g = bh is the gross area of the concrete section and p = 2( b + h ) is the perimeter of the gross concrete cross section 13…”
Section: Analytical Modelingmentioning
confidence: 99%